Генетична структура української популяцiї свиней породи велика бiла за геном естроген-рецептора - Коновал, О.М.; Костенко, С.О.; Спиридонов, В. Г.; Мельничук, С.Д.; Григорюк, І.П. (Видавничий дім "Академперіодика" НАН України, 2008)
The polymorphism of Large White pig breed (Sus scrofa) by ESR gene has been investigated by PCR RLFP. The frequency of desirable genotype ВВ is fluctuated from 4.5 to 27.9%.